Laparoscopic Treatment of Intrauterine Fallopian Tube Incarceration - William Kondo; Rafael Frederico Bruns; Marcelo Chemin Nicola; Reitan Ribeiro; Carlos Henrique Trippia; Monica Tessmann Zomer (Case Reports in Obstetrics and Gynecology)
Herniation of the pelvic structures into the uterine cavity (appendix vermiformis, small bowel, omentum, or fallopian tube) may occur after uterine perforation. In this paper, we describe one case of intrauterine fallopian tube incarceration treated by means of laparoscopic surgery.